Visual load does not decrease the auditory steady‐state response to 40‐Hz amplitude‐modulated tones. (18th September 2020) - Szychowska, Malina; Wiens, Stefan
Abstract: The auditory pathway consists of multiple recurrent loops of afferent and efferent connections that extend from the cochlea up to the prefrontal cortex. The early‐filter theory proposes that these loops allow top‐down filtering of early and middle latency auditory responses. Furthermore, the adaptive filtering model suggests that the filtering of irrelevant auditory stimuli should start lower in the pathway during more demanding tasks. If so, the 40‐Hz auditory steady‐state responses (ASSRs) to irrelevant sounds should be affected by top‐down crossmodal attention to a visual task, and effects should vary with the load of the visual task. Because few studies have examined this possibility, we conducted two preregistered studies that manipulated visual load (Study 1: N = 43, Study 2: N = 45). Study 1 used two levels (low and high), and Study 2 used four levels (no, low, high, and very high). Subjects were asked to ignore a 500‐Hz task‐irrelevant tone that was amplitude‐modulated to evoke 40‐Hz ASSRs. Results from Bayesian analyses provided moderate to extreme support for no effect of load (or of a task) on ASSRs. Results also supported no interaction with time (i.e., over blocks, over minutes, or with changes in ASSRs that were synchronized with the onset of the visual stimuli). Further, results provided moderate support for no correlation between the effects of load and working memory capacity. Because the present findings support the robustness of ASSRs against manipulations of crossmodal attention, they are not consistent with the adaptive filtering model. Abstract : The adaptive filtering model suggests that the filtering of irrelevant auditory stimuli should start lower in the auditory pathway during more demanding tasks. Two preregistered studies ( N = 43, N = 45) examined the effects of visual perceptual load (from no to very high) on the 40‐Hz auditory steady‐state response (ASSR) to a task‐irrelevant tone. Bayesian analyses provided evidence for no effect of load. This robustness of ASSR against manipulations of crossmodal attention is not consistent with the adaptive filter model.